The process of sending imported goods through a freight forwarder - Meliana Santi (Lead Journal of Economy and Administration, 2022)
In managing the process of sending imported goods it is not uncommon to have problems, and the problems that usually arise from companies engaged in logistics services are in terms of the long bureaucracy in processing documents so that the process of sending goods experiences delays, and inaccuracies in checking documents so that they have to change data. This study used a qualitative method by collecting data through interviews, observations and related documents. The results of this study are that in the import shipping process at CV Jaya logistics dynasty including receiving import documents, making a PIB draft on PPJK, calling the arrival of the plane, paying PIB taxes, requesting manifests, requesting PIB transfers and waiting for tracking responses, paying D/O, preparing import documents, paying warehouse rent or stacking fees, sending goods to the warehouse, confirming receipt of goods and making invoices. This is important in carrying out the handling process at CV Jaya logistics dynasty. On handling goods.